The Behaviors of the Preparation Before Retirement Preparation Office of the Bangkok Metropolitan Administration Civil Service Commission Preparation - Wonglim, Parichat; Noppanatwongsakorn, Rachen (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research were (1) to study the retirement preparation behavior of ordinary Bangkok civil servants. under the Office of the Bangkok Civil Service Commission, classified by personal characteristics (2) to study the awareness of the preparation of the Bangkok Metropolitan Administration officials under the Office of the Bangkok Civil Service Commission; and (3) Recommend appropriate guidelines for retirement preparation of the Bangkok Metropolitan Administration under the Office of the Bangkok Civil Service Commission The results showed that (1) Personal characteristics of Bangkok Metropolitan Administration officials Most of the respondents were female, aged 41-50 years, bachelor’s degree, single status, 11-20 years of employment, average monthly income. 15,001-20,000 baht and job position level operating level (2) There was a high level of awareness of the overall preparation for retirement. and when considering the awareness of each aspect, it was found that ordinary Bangkok officials have a mental awareness higher than other areas, followed by health awareness and financial awareness, respectively. is lower than the other side, and (3) Recommendations on appropriate guidelines for preparing for retirement of Bangkok civil servants under the Office of the Bangkok Civil Service Commission Residential awareness, the issue with the most frequencies, was to consider the suitability of income with housing in order not to burden yourself too much and the location of the residence Must be convenient to travel Not far from the community from friends or close relatives housing preparation behavior The most frequent is living. You should plan in advance with whom you will spend your retirement. Live with spouse Live with relatives Live with children in order to help each other or being alone alone, followed by building good relationships with family, community and society is important. in coexistence and participation with the community to improve and develop the environment